Chronic malnutrition and anemia in children under 5 years of indigenous households of Peru - Analysis of Demographic and Health Survey 2013. - Flores Bendezú, Janet (2015)
Introduction: Child chronic malnutrition and anemia represent a major public health problem whose consequences are manifested throughout the life cycle. The Peruvian State is characterized by hosting one of the largest ethno-cultural wealth of the Americas, being the Peruvian Amazon region the one that has the greatest diversity of indigenous groups in the country. Objective: To determine the prevalence of chronic malnutrition and anemia in children under 5 years of indigenous households in Peru. Design: Secondary analysis of data from the Demographic and Health Survey (DHS) 2013, National Institute of Statistics and Informatics. Institution: Second Specialization in Public Nutrition, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Children under 5 years of households from the Amazon region where the primary language is indigenous. Main outcome measures: Chronic malnutrition (<-2 Z-scores for height for age) and anemia (<11 g/dL hemoglobin adjusted for altitude). Results: Chronic malnutrition affected 43% and anemia 43.5% of children under 5 years of indigenous households. There was no statistically significant association between chronic malnutrition and sex or age of the child, nor between anemia and gender of the child; however an association between the child's age and anemia was found (p<0.001). Conclusions: Chronic malnutrition and anemia were high in children under 5 years of indigenous households in the Amazon region of Peru, evidencing the large disparities in poverty, basic services and health in indigenous children.